Coronary-Pulmonary Artery Fistulas: A Systematic Review. Issue 6 (November 2016) - Verdini, Daniel; Vargas, Daniel; Kuo, Anderson; Ghoshhajra, Brian; Kim, Phillip; Murillo, Horacio; Kirsch, Jacobo; Lane, Michael; Restrepo, Carlos
Abstract : Purpose: Coronary-pulmonary arterial fistulas (CPAFs) are rare coronary artery anomalies that have been described only in limited case reports. This study aims to evaluate the clinical presentation and imaging findings of CPAFs collected from 6 participating medical centers along with CPAFs reported in the literature, to discern any general trends present in CPAFs. Materials and Methods: A total of 25 cases of CPAF diagnosed by coronary computed tomography angiography were collected across 6 participating institutions. In addition, utilizing a PubMed literature search, 78 additional CPAF cases were obtained. The imaging findings and relevant clinical history were reviewed. Results: Of the 103 CPAF patients, 60 (63% of patients with sex known) were male, with ages ranging from newborn to 88 years (mean=46.1 y). The most common symptoms reported were chest pain (n=40, 39%) and dyspnea (n=26, 25%), with a murmur as the most common physical examination finding (n=38, 37%). The most common coronary artery of origin for a CPAF was the left main/left anterior descending (n=87, 84%), followed by the right coronary artery (n=39, 38%). The fistula most commonly terminated in the main pulmonary artery (n=92, 89%). Multiple CPAFs were present in 46 cases (45%). Coronary artery aneurysms were identified in 20 cases (19%). Pediatric CPAF cases were usually associated with pulmonary atresia with ventricular septal defect. Conclusions: CPAFs are seen in a variety of clinical settings, from infants with advanced congenital heart disease to elderly patients who have undergone revascularization surgery. Although coronary artery fistulas have previously been described as rarely involving multiple coronary arteries, with the right coronary artery being most often involved, our series demonstrates that multiple fistulas are commonly present, with the most common pattern being between the left main/left anterior descending and the main pulmonary trunk.